New Record of Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae) Attacking Starfruit (Averrhoa carambola L.) in Sinop, Mato Grosso, Brazil - Pires, Evaldo Martins; Bonaldo, Solange Maria; Ferreira, João Alfredo Marinho; Soares, Marcus Alvarenga; Candan, Selami (EntomoBrasilis, 2011)
Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae) is a phytophagous bug widely found in the American continent. This species is associated with different crops, which they use to establish due to the favorable food supply and conditions for their development. The aim of this work was to record the occurrence of L. zonatus attacking starfruit in Sinop, Mato Grosso, Brazil and report a new host plant to this bug species. Adults and immatures were found between September and November of 2009 feeding on starfruit (Averrhoa carambola L.) in Sinop, Mato Grosso, Brazil. The attack affected the fruit quality, allowing other insects, such as some Phoridae species, to access to the fruit secretions through the hole made by the rostrum of this bug and then causing damage to the quality of the fruit. Novo Registro de Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae) Atacando Frutos de carambola (Averrhoa carambola L.) em Sinop, Mato Grosso, Brasil Resumo. Leptoglossus zonatus (Dallas) (Heteroptera: Coreidae) um percevejo fitófago amplamente encontrado no continente Americano. Essa espécie encontra-se associada a diversas culturas agrícolas, onde se estabelecem devido a oferta de alimento e de condições favoráveis ao seu desenvolvimento. O objetivo foi registrar a ocorrência de L. zonatus atacando frutos de carambola em Sinop, Mato Grosso, Brasil e relatar nova planta hospedeira para esse percevejo. Adultos e imaturos foram encontrados durante os meses de setembro a novembro de 2009, atacando frutos de carambola (Averrhoa carambola L.) no município de Sinop, Mato Grosso, Brasil. O ataque desse percevejo prejudica a qualidade dos frutos, permitindo que outros insetos como dípteros da família Phoridae tenham acesso a secreções do fruto pelo orifício feito pelo estilete desse percevejo, causando assim, danos na qualidade da carambola.